Situation analysis of medical laboratories in primary health centres - Suberi, Radhika S. (International Journal Of Community Medicine And Public Health, 2021)
Background: This study was conducted with the objective to assess the medical laboratories attached with primary health centres (PHCs) focusing on the current needs, gaps and to understand the utilization pattern of the laboratory services. There are hardly any relevant studies that are known to have investigated the functioning of laboratories attached with PHCs based on quality of service they are providing. Methods: This study was a cross sectional study based on observations and assessment made at 33 randomly selected medical laboratories attached with PHCs in Ahmedabad district, Gujarat. Checklist adapted from National Quality Assurance Standards (NQAS) and Indian Public Health Standards (IPHS) were used as a tool for data collection. Results: Though all the laboratories have been found to be functioning effectively based on the indicators in this study, some of the laboratories were not performing basic important tests like rapid plasma reagin (RPR) (18%) and hepatitis B surface antigen (HbSAg) (21%). None of the laboratories attached to the PHCs under study performed Widal test. There was very low utilization of urinary pregnancy test (UPT) (1.81%) in the first quarter of the year. Conclusions: Although most of the indicators reflect satisfactory performance of the laboratories, there exists certain gaps and needs that are essential in provision of quality laboratory services in the primary level of health care. The laboratory information management system (LIMS) was the major issue in the laboratories.